Social contingencies that hinder college teacher’s engagement in quality relationships with their students - Vieira-Santos, Joene; Henklain, Marcelo Henrique Oliveira (Perspectivas em Análise do Comportamento, 2017)
Professor’s primary role is to promote students learning, a challenging task that involves several factors, including professor and student relationship. equality of this relationship has been the subject of several scientific studies that demonstrate its relevance to student’s learning. e question that arises is whether the contingencies related to professor’s work promote their engagement in quality relations with their students. In this essay, we sought to identify some contingencies related to professor’s work that seems to hinder the acquisition and maintenance of the behavior of establishing quality relations with their students. We analyzed contingencies related to time management, professor’s educative social skills, student’s attitude towards to their professor, conflicts between professors and students, institutional aspects in academic context, professor’s discrimination deficit about the effect that their behavior has upon students’ and public policies related to undergrad education. We hope that this essay helps and promotes the process of establishing the quality of professors and students’ relationship as a value to be pursued by students, professors, educational administrators and public policies, contributing to foment the necessary changes to a quality education for everyone.